A re-examination of the validity of the typological view of Mandarin as a topic-prominent language / Zhu Lanhui - Zhu , Lanhui (2018)
The typological view of Mandarin being a Topic-prominent language (henceforward TP language) as proposed by Li and Thompson in the 1980s has been exerting great influence on Mandarin-related studies ever since. Even until present, Mandarin is still chosen as benchmark to investigate whether a certain language falls under the Topic-prominent language category. The typological view on Mandarin is generally considered to be valid. However, the challenging doubts on the validity of the typological view on Mandarin have existed since 1984. Although quite a few studies have questioned the validity of the typological view of Mandarin as a TP language, there is only the one quantitative study by Chen and Gao based on written data in 2000 to prove that the typological view on Mandarin cannot hold true. In the line of extended quantitative research, the current study purports to re-examine whether the typological view of Mandarin as a TP language can still hold true. In order to achieve this objective, the current study draws upon 50 spontaneous interviews as its corpus from a talk show entitled Date with Luyu. By drawing on theories from Systemic Functional Linguistics, the quantitative findings suggest that in 34,458 clauses generated from 50 transcribed interviews, the occurrence and the portion of Topic-Comment sentences (henceforward TCS) used as evidence to show that Mandarin is a TP language is 956 and 2.77%. The qualitative findings suggest that to consider Topic as a syntactic notion in the so-called TCS is problematic. Both quantitative and qualitative findings of the current study, therefore, cannot support the typological view on Mandarin. Significantly, the findings of the the current study shed light on languge typology and Mandarin-related studies in general.